ANALISIS SEMANGAT KERJA KARYAWAN PT. JASAMARGA TOLLROAD OPERATOR DI BALIKPAPAN - SAMARINDA - Tamzil Yusuf; Yudi Hendrawan; Elwyn Adrian Kailola; Rima Rima; Setia Dewi; Irna Febriyanti (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study was to determine the effect of motivation, work environment, and communication on employee morale at PT. Jasamarga Tollroad Operator in Balikpapan - Samarinda. This research was conducted at PT. Jasamarga Tollroad Operator in Balikpapan - Samarinda, with 50 respondents, this research method uses quantitative methods. Collecting data by means of observation and distributing questionnaires via google form. The data analysis technique used is multiple linear analysis by performing instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of motivation, work environment, and communication had a positive and significant effect on employee morale at PT. Jasamarga Tollroad Operator in Balikpapan - Samarinda.